2016
DOI: 10.1016/j.jcin.2015.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Versus Surgical Closure of Atrial Septal Defects in Children

Abstract: Both transcatheter and surgical ASD closure had excellent short-term outcomes, but transcatheter procedures had lower lengths of stay, rates of infection, and complications, resulting in lower overall costs. For children who are eligible, transcatheter ASD closure provides better short-term value than surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 24 publications
5
42
0
6
Order By: Relevance
“…The approach to O-ASD has been consistent over the time period. As has been demonstrated in previous studies, the factors that result in a higher cost after operative procedures are primarily length of stay and adverse events (while transcatheter therapies are more expensive as a result of the cost of the device itself) (5,19,36). We expected that attention to these issues would have resulted in efforts to reduce post-operative length of stay.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…The approach to O-ASD has been consistent over the time period. As has been demonstrated in previous studies, the factors that result in a higher cost after operative procedures are primarily length of stay and adverse events (while transcatheter therapies are more expensive as a result of the cost of the device itself) (5,19,36). We expected that attention to these issues would have resulted in efforts to reduce post-operative length of stay.…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies have demonstrated that TC-ASD has lower cost and shorter LOS than O-ASD(5,36). Over the study period, there were no significant changes in either following TC-ASD.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Minimal invasive therapies such as transcatheter aortic valve implantation (TAVI), devices for atrial septal defects (ASD), or clips to treat mitral regurgitation have become alternatives for surgical procedures. [1][2][3][4] As the expanding portfolio of interventional cardiology comes with new challenges, a need for imaging tools to support the cardiologist has arisen.…”
Section: Introductionmentioning
confidence: 99%